2022
DOI: 10.1021/acs.jcim.2c00419
|View full text |Cite
|
Sign up to set email alerts
|

Design of Peptides that Fold and Self-Assemble on Graphite

Abstract: The graphite–water interface provides a unique environment for polypeptides that generally favors ordered structures more than in solution. Therefore, systems consisting of designed peptides and graphitic carbon might serve as a convenient medium for controlled self-assembly of functional materials. Here, we computationally designed cyclic peptides that spontaneously fold into a β-sheet-like conformation at the graphite–water interface and self-assemble, and we subsequently observed evidence of such assembly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Furthermore, studying the inter-and intramolecular interactions is highly challenging as the key contributors to the self-organized nanostructures on surfaces. 6,18,19 The solid binding peptides, selected through directed evolution methodologies, [1][2][3][4]9 may provide a means to address these questions, as demonstrated by previous studies. Normally, the peptide is selected, from the pool of peptides with billions of different sequences, for its exclusive affinity to the relevant solid surface.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, studying the inter-and intramolecular interactions is highly challenging as the key contributors to the self-organized nanostructures on surfaces. 6,18,19 The solid binding peptides, selected through directed evolution methodologies, [1][2][3][4]9 may provide a means to address these questions, as demonstrated by previous studies. Normally, the peptide is selected, from the pool of peptides with billions of different sequences, for its exclusive affinity to the relevant solid surface.…”
Section: Introductionmentioning
confidence: 96%
“…The structural and self-organization characteristics of these small biomolecules are largely unknown, and the structures formed are unpredictable, thereby, making the design of such self-organized molecular architectures currently impractical. One of the reasons for this unpredictability, until recently, has been due to the uncoupled nature of the peptide–solid systems studied so far, i.e., random peptide sequence used that assemble in solution and land on the surface, or self-organize, often by chance, on arbitrary solid surfaces. More importantly, short peptides are labile and have intrinsically disordered structural folding patterns, which limits the prediction of their conformation characteristics and, therefore, their interaction with solid surfaces. Furthermore, studying the inter- and intramolecular interactions is highly challenging as the key contributors to the self-organized nanostructures on surfaces. ,, …”
Section: Introductionmentioning
confidence: 99%
“…We note in passing that recent work [ 45 ] has indicated that even short peptides can require run lengths well in excess of 300 ns to fold. However, in the case of Aβ 1-42 , the structure transforms quickly and completely from the initial PDB secondary structure containing two α-helices (see Figure S3a , which was obtained as a 3D NMR structure in an apolar solution) to a β-sheet folded structure in SPC water.…”
Section: Resultsmentioning
confidence: 95%
“…Before these simulations, we cyclized the peptides using a head-to-tail amide linkage, which can improve proteolytic and conformational stability. [23][24][25][26][27][28] We characterized the strength of binding by tracking the time that the peptide stayed bound during the simulation and estimated binding free energy using the MM-GBSA method. 49 While neither of these characterizations are rigorous, they provided an efficient means to eliminate unpromising candidates with a small investment of computer time.…”
Section: Screening Of Peptide Sequencesmentioning
confidence: 99%
“…23,25 Furthermore, crosslinks of various chemistries (referred to as "staples") can be used to cyclize peptides in ways never found in nature. 18,24 Cyclization also helps to stabilize the secondary structure of peptides [26][27][28] and can also improve binding affinity by reducing the entropy of the unbound state and therefore the entropy lost upon binding. 12,29,30 Computational protein design tools have matured over the last decade, enabling rational design of peptides with desired structure and function.…”
Section: Introductionmentioning
confidence: 99%